Construction of Teaching Module Structure With Deep Learning Approach For Secondary School Teachers - Julimawati; Emas Marlina; Heru Sujiarto; Diana Silaswati; Wintarsih (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This community service was motivated by the fact that some teachers, particularly those at the junior high school level, still do not understand how to develop teaching modules using the deep learning approach, thus requiring guidance for these teachers. The purpose of this guidance is to facilitate junior high school teachers in developing teaching modules using the deep learning approach, with the subject of guidance being teachers at SMP STMC 4245 Baleendah, Bandung. This guidance method was carried out through problem identification, socialization of the deep learning approach, discussions and practicums on developing teaching modules using the deep learning approach, evaluation and reflection. The results of the activity showed that the guidance went well and received a positive response from the participants, where 86% of teachers stated that they really enjoyed the activity, 11% stated that they enjoyed it, and 3% still needed further guidance. The evaluation results also showed an increase in teachers' understanding and skills in developing teaching modules based on Deep Learning, as indicated by an increase in posttest results compared to the pretest. Teachers were able to integrate the principles of mindful learning, meaningful learning, and joyful learning into teaching modules that were designed according to the characteristics of their respective subjects. Thus, the coaching activities have proven effective in improving teachers' competency in developing Deep Learning-based teaching modules, thereby supporting the implementation of more meaningful, active, and student-centered learning.